2008
DOI: 10.1606/1044-3894.3734
|View full text |Cite
|
Sign up to set email alerts
|

Familias in the Heartland: Exploration of the Social, Economic, and Cultural Realities of Latino Immigrants

Abstract: This survey of 957 Latino immigrant adults in urban and suburban communities in the greater Kansas City metropolitan area explores the migration experiences, employment contexts, family structures, and integration processes of an emerging and rapidly growing immigrant population.The study is an example of community-driven research, conducted by a nonprofit community development and immigrant rights organization in close partnership with local immigrant leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Respondents indicated that they changed jobs due to better pay, exploitation, termination, transportation issues, and childcare. Finally, Mexican women earned lower wages than men in the Northeast (Fuentes, 2007) but not in the Midwest (Lewis, 2008).…”
Section: Immigrant Worker Characteristicsmentioning
confidence: 99%
“…Respondents indicated that they changed jobs due to better pay, exploitation, termination, transportation issues, and childcare. Finally, Mexican women earned lower wages than men in the Northeast (Fuentes, 2007) but not in the Midwest (Lewis, 2008).…”
Section: Immigrant Worker Characteristicsmentioning
confidence: 99%
“…In recent years, family scholars have documented the opportunities and challenges Latino immigrant families experience in rural destinations. Immigrants typically describe a number of challenges, including language barriers, discrimination, transportation issues, and lack of benefits due to low‐paying, high‐turnover jobs (e.g., Cristancho, Garces, Peters, & Mueller, 2008; Lewis, 2008). At the same time, they describe sources of strength that may foster positive adjustment, such as strong family connections and the flexibility to adapt to life in a new land (e.g., Campbell, 2008; Ornelas, Perreira, Beeber, & Maxwell, 2009; Parra‐Cardona, Bulock, Imig, Villarruel, & Gold, 2006).…”
mentioning
confidence: 99%
“…Individuals—especially immigrants—are frequently attracted to geographic areas where there are known family members, friends, or others of similar ethnic background (Lewis 2008). These concentrated areas of an ethnic group may emerge as a support network vis-à-vis limited familiarity with the culture and institutions of the host society.…”
Section: Social and Structural Nuances Of Latinx Enclavesmentioning
confidence: 99%
“…Even when they achieve high educational levels, Latinxs still receive less financial rewards in their earnings compared with whites (Lewis 2008). Furthermore, due to their disproportionately lower earnings in the workforce, the Latinx population has “lower returns” from living in enclaves compared with other ethnic groups (like Asians), who have higher earnings and relatively fewer socio-economic barriers (Edin, Fredriksson, and Åslund 2003).…”
Section: Social and Structural Nuances Of Latinx Enclavesmentioning
confidence: 99%
See 1 more Smart Citation